2001
DOI: 10.1002/ijc.10121
|View full text |Cite
|
Sign up to set email alerts
|

Significance of vascular endothelial growth factor (VEGF)/soluble VEGF receptor‐1 relationship in breast cancer

Abstract: Angiogenesis, the formation of new blood vessels, is controlled by a balance between positive and negative endothelial regulatory factors. Soluble vascular endothelial growth factor receptor-1 (sVEGFR1), a naturally occurring soluble form of VEGFR1, is a negative counterpart of the vascular endothelial growth factor (VEGF) signaling pathway, which has been characterized as one of the most important endothelial regulators in human tumor angiogenesis. In our study, we examined the expression of sVEGFR1 in 110 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…VEGF-A and VEGF-C are the major factors in the progression and metastasis of many malignancies as well as the important risk factors for prognosis (Otrock et al 2007;Hicklin and Ellis 2005;Toi et al 2002); however, there were few reported studies about the prognosis signiWcance of VEGF receptors in tumor or the peritumoral area. We used an unsupervised hierarchical clustering analysis to classify the 107 HCC patients into meaningful prognostic groups based on the minimal set of biomarkers of VEGF/ VEGFR.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A and VEGF-C are the major factors in the progression and metastasis of many malignancies as well as the important risk factors for prognosis (Otrock et al 2007;Hicklin and Ellis 2005;Toi et al 2002); however, there were few reported studies about the prognosis signiWcance of VEGF receptors in tumor or the peritumoral area. We used an unsupervised hierarchical clustering analysis to classify the 107 HCC patients into meaningful prognostic groups based on the minimal set of biomarkers of VEGF/ VEGFR.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter could be used in practice to assess the degree of severity of PAD, which is the subject of the current research (Rość et al, 2014). The studies by Toi et al (2002) involving patients with breast cancer and the studies by Yamaguchi et al (2007) concerning individuals suffering from colorectal carcinoma, were focused on analyzing the sVEGFR-1/VEGF ratio in terms of clinical parameters and prognosis of cancer. This study showed stronger angiogenic inhibition capacity demonstrated by the ratio of concentrations (sVEGFR-1/ VEGF-A and sVEGFR-2/VEGF-A) in the control group in comparison with PAD subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…However, this concept has now been challenged by recent reports showing that some cancer cells express VEGF receptors on their surfaces in vitro and in vivo, and that in several tumor cell types, including leukemia and melanoma cells, VEGF acts as an autocrine survival factor [22,23]. Although breast cancer cell lines express both VEGF and the VEGF receptors VEGFR1, VEGFR2, and NRP1 [11], the expression of these receptors in primary breast tumors is controversial [12,13,24–28]. Dales et al [12] reported that VEGFR1 and VEGFR2 were strongly expressed in endothelial cells within blood microvessels, and weakly expressed in tumor cells in a series of 918 patients.…”
Section: Discussionmentioning
confidence: 99%